Biofluid spectroscopic disease diagnostics: A review on the processes and spectral impact of drying. Issue 4 (5th March 2018) - Cameron, James M.; Butler, Holly J.; Palmer, David S.; Baker, Matthew J.
Abstract : The complex patterns observed from evaporated liquid drops have been examined extensively over the last 20 years. Complete understanding of drop deposition is vital in many medical processes, and one which is essential to the translation of biofluid spectroscopic disease diagnostics. The promising use of spectroscopy in disease diagnosis has been hindered by the complicated patterns left by dried biological fluids which may inhibit the clinical translation of this technology. Coffee‐ring formation, cracking and gelation patterns have all been observed in biofluid drops, and with surface homogeneity being a key element to many spectroscopic techniques, experimental issues have been found to arise. A better understanding of the fundamental processes involved in a drying droplet could allow efficient progression in this research field, and ultimately benefit the population with the development of a reliable cancer diagnostic. Abstract : Over the past 2 decades, researchers have examined the processes involved in evaporating liquid drops, however, the phenomenon is still not completely understood. Homogeneous drop deposition is key in many applications, but complex patterns observed from dried biofluid drops currently inhibits clinical translation of various techniques, namely spectroscopic disease diagnostics. A better understanding of the fundamental processes involved in a drying droplet could enhance the development of reliable cancer diagnostics.